2010
DOI: 10.1111/j.1365-2036.2010.04537.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomised clinical trial: a comparative dose-finding study of three arms of dual release mesalazine for maintaining remission in ulcerative colitis

Abstract: SUMMARY BackgroundComparative data regarding different regimens of oral mesalazine (mesalamine) for maintaining remission in ulcerative colitis are limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
14

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 20 publications
0
45
0
14
Order By: Relevance
“…Por ello, recomienda el uso de estos fármacos para la inducción de la remisión del paciente con brote leve-moderado de CU a dosis mínima de 2,4 g/día y probablemente óptima ≥ 3 g/día en una única dosis diaria. Respecto a la dosis de mantenimiento con estas formulaciones, el estudio de Kruis et al 37 sugiere (con evidencia moderada según la clasificación GRADE) que una toma de 3 g/día de Salofalk ® es superior a 1,5 g/día, sin observar diferencias significativas en la seguridad entre ambos grupos. Los estudios que comparan las diferentes dosis de Mezavant ® (2,4, 3,2 y 4,8 g) para el tratamiento del brote de la CU no han demostrado diferencias significativas respecto a la remisión clínica, pero se ha observado una tendencia a una mayor remisión endoscópica con las dosis más altas, aunque las diferencias no alcanzaron significación estadística 13 .…”
Section: Discussionunclassified
“…Por ello, recomienda el uso de estos fármacos para la inducción de la remisión del paciente con brote leve-moderado de CU a dosis mínima de 2,4 g/día y probablemente óptima ≥ 3 g/día en una única dosis diaria. Respecto a la dosis de mantenimiento con estas formulaciones, el estudio de Kruis et al 37 sugiere (con evidencia moderada según la clasificación GRADE) que una toma de 3 g/día de Salofalk ® es superior a 1,5 g/día, sin observar diferencias significativas en la seguridad entre ambos grupos. Los estudios que comparan las diferentes dosis de Mezavant ® (2,4, 3,2 y 4,8 g) para el tratamiento del brote de la CU no han demostrado diferencias significativas respecto a la remisión clínica, pero se ha observado una tendencia a una mayor remisión endoscópica con las dosis más altas, aunque las diferencias no alcanzaron significación estadística 13 .…”
Section: Discussionunclassified
“…In fact, there is some evidence that higher doses may be more effective. Thus, in a 1-year prospective controlled trial, per protocol analysis of data demonstrated that 3.0 g of oral mesalamine (Salofalk ® ) once daily was superior to 1.5 g once daily or 0.5 g three times weekly (86 %, 67 % and 78 %, respectively, p = 0.024) [ 32 ]. In a meta-analysis of seven randomised clinical trials, 5-ASA doses greater than 2.0 g/day were more likely to reduce the risk for relapse for 6-12 months compared to doses lower than 2.0 g/day, but the quality of the trials that were subjected to analysis was not optimal [ 22 ].…”
Section: Aminosalicylates Sulfasalazine and Oral Aminosalicylatesmentioning
confidence: 94%
“…In patients with proctitis or left-sided colitis local mesalamine application and in patients with extensive disease oral mesalamine therapy is recommended to maintain remission. 34 Maintenance therapy with mesalamine is discussed to have an additional chemopreventive effect with reduced colorectal cancer risk. 35 Azathioprine is recommended in steroidrefractory or-dependent patients.…”
Section: Ulcerative Colitismentioning
confidence: 99%